Recreational fisheries within the Portofino MPA and surrounding areas (Ligurian Sea, Western Mediterranean Sea) - VENTURINI, SARA; MEROTTO, LORENZO; CAMPODONICO, PIETRO; CAPPANERA, VALENTINA; FANCIULLI, GIORGIO; CATTANEO-VIETTI, RICCARDO (Mediterranean Marine Science, 2019)
In the Mediterranean Sea, recreational fishing is a popular activity and anglers catch a significant amount of fish which could represent more than 10% of the total harvesting in a littoral area. The Portofino Marine Protected Area, established in 1999 in the Ligurian Sea (North-Western Mediterranean), traditionally hosts a well-developed recreational fishery. Aim of this study has been to characterize the activities of the local anglers, analysing their annual harvesting within and around the Portofino MPA and the species composition of the catches. This was possible studying data from the mandatory anglers’ logbooks, and through interviews and surveys at sea. In 2015, the 340 checked anglers fished, in average, 1 kg/day, on average, mainly by trolling or handlining systems. Each fisherman, during 25 (± 21) trips, fished approximately 25 kg/year, for a total harvesting of about 8-9 t/year. Seriola dumerili, with 230 kg/year, was the species most caught in terms of biomass. It was followed by Coryphaena hippurus (130 kg/year). In addition, the analysis of catches occurring during local fishing competitions organized off the MPA limits suggested a harvesting capacity for each angler varying between 0.7 and 1.1 kg/angler per day, depending on the used gear (handlining, trolling, spear-guns). Finally, 36% of the anglers claimed to hook often the hard bottom seabed, often losing nylon lines. Consequently, the Management Body of the Portofino MPA has been advised to suspend recreational fishing activities in the most busy areas for a period of two years, calling for a complete removal of the lost fishing gears.